2020
DOI: 10.1021/acsami.0c00873
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Thermoelectric Performance of Polycrystalline SnSe by Decoupling Electrical and Thermal Transport through Carbon Fiber Incorporation

Abstract: Thermoelectric (TE) materials have attracted extensive interest because of their ability to achieve direct heat-to-electricity conversion. They provide an appealing renewable energy source in a variety of applications by harvesting waste heat. The record-breaking figure of merit reported for single crystal SnSe has stimulated related research on its polycrystalline counterpart. Boosting the TE conversion efficiency requires increases in the power factor and decreases in thermal conductivity. It is still a big … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Carbon fibers acted as good electrical conductors and simultaneously reduced the lattice thermal conductivity (0.22 W m −1 K −1 ) by enhancing the scattering due to the high density of interface, which led to ZT ∼ 1.3 at 823 K. This inclusion increased the mechanical stability of the device. 119 The thermoelectric parameters of poly-crystals SnSe are tuned by sintering temperature in the spark plasma sintering (SPS). Zhang et al 120 varied the sintering temperature from 300 to 650 °C in SPS and showed that vacancy defects (Se, Sn, and Se–Sn) were responsible for the performance variation.…”
Section: Various Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon fibers acted as good electrical conductors and simultaneously reduced the lattice thermal conductivity (0.22 W m −1 K −1 ) by enhancing the scattering due to the high density of interface, which led to ZT ∼ 1.3 at 823 K. This inclusion increased the mechanical stability of the device. 119 The thermoelectric parameters of poly-crystals SnSe are tuned by sintering temperature in the spark plasma sintering (SPS). Zhang et al 120 varied the sintering temperature from 300 to 650 °C in SPS and showed that vacancy defects (Se, Sn, and Se–Sn) were responsible for the performance variation.…”
Section: Various Applicationsmentioning
confidence: 99%
“…Thus, this material demands greater attention and research to achieve predicted ZT . Researchers should pay attention to new approaches to improve the SnSe thermoelectric material's performance like nano-inclusion, 153 decoupling of interrelated parameters, 119 nano-structuring and texturing, etc. Simultaneously, the theoretical study should be carried out to optimize the threshold values of the parameters.…”
Section: Various Applicationsmentioning
confidence: 99%
“…[ 18 , 19 , 20 , 21 ] The maximum ZT was increased up to ≈0.8 at high T = 800 K for Na 1% doped SnSe. [ 21 ] Even for that, the ZT has been limited to < ≈0.3 at low T ≤ 573 K. Therefore, the additional nano‐structuring process, that is, the addition of precipitates such as Ag 8 SnSe 6 , PbSe, and carbon fiber, [ 22 , 23 , 24 ] has been adopted to introduce phonon scattering centers to reduce κ lat , which realized the higher ZT ≈ 1.3 at high T = 773–823 K and ≈0.6 at low T = 573 K in polycrystalline SnSe. Thus, the well improved thermoelectric SnSe usually needs complicated processes not only for a fine optimization of n and PF, but also a selective decrease of κ lat in order to maximize the ZT .…”
Section: Introductionmentioning
confidence: 99%
“…σ is the electrical conductivity, which can be expressed as σ = neμ, where μ is electron mobility, and n is carrier concentration. Thermal conductivity κ = κ e + κ l is composed of the electronic thermal conductivity and the lattice thermal conductivity κ [ 5 , 6 , 7 , 8 , 9 ]. Generally, a high ZT value indicates excellent thermoelectric performance, which means a high Seebeck coefficient S and electrical conductivity σ and a low thermal conductivity κ.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is very difficult to optimize multiple parameters simultaneously due to the interdependence of the three parameters [ 7 , 10 ]. Over the past few decades, numerous studies have focused on exploring a rational design to improve TE thermoelectric property, such as resonant doping, band convergence, and energy filtering effects to enhance the power factor, solid solutions, Nano structuring, and all-scale hierarchical structuring for reducing κ [ 1 , 6 , 9 , 11 ]. Additionally, it is worth noting that the mechanical properties, flexibility, stretchability, and toxicity of thermoelectric materials should also be considered, since the wearable TEGs can attach conformably onto the skin and prevent heat losses during energy transfer from the human body [ 3 ].…”
Section: Introductionmentioning
confidence: 99%